Antimicrobial activity of nisin, thymol, carvacrol and cymene against growth of Candida lusitaniae. (January 2015) - Aznar, Arantxa; Fernández, Pablo S; Periago, Paula M; Palop, Alfredo
Yeasts are tolerant to acid pH values, are able to grow in anaerobic media and have minimum nutrition requirements. These capabilities enable them to survive and even grow in foods prepared from acid fruits or vegetables. Among yeasts, Candida is one of the genus most frequently isolated from fruit juices. Bacteriocins and essential oils from spices and aromatic herbs are an alternative to preservatives and other technological treatments and have the advantage that their natural origins do not lead to consumer rejection. However, before the food industry uses them on a large scale, it is necessary to know their effects on microorganisms. The objective of this research was to study the effect of different concentrations of nisin, thymol, carvacrol and cymene on the growth of Candida lusitaniae in pH 5 broth at 25 ℃, and their potential uses as food preservatives. The addition of nisin at the concentrations tested (up to 3 µmol L −1 ) did not affect the yeast growth. Thymol, carvacrol and cymene completely inhibited the yeast growth at concentrations over 1 mM for at least 21 days at 25 ℃. Below this concentration, inhibitions on yeast growth were observed at increasing concentrations. The effect of thymol was also proved in tomato juice. This study indicates the potential use of essential oils for preservation of minimally processed foods.